2003
DOI: 10.1136/gut.52.7.922
|View full text |Cite
|
Sign up to set email alerts
|

A randomised prospective comparison of the Flamingo Wallstent and Ultraflex stent for palliation of dysphagia associated with lower third oesophageal carcinoma

Abstract: Background: Covered metallic oesophageal stents offer effective palliation of malignant oesophageal strictures. However, first generation devices were associated with a high rate of migration, particularly when used in the lower oesophagus. Aim: To compare the rate of complications and palliative effect of two newer covered metallic oesophageal stents. Patients and methods: We performed a prospective randomised study using two of these newer stent designs in the treatment of malignant lower third oesophageal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 22 publications
9
96
0
5
Order By: Relevance
“…In patients with stent placement across the GEJ, the migration rate was even higher (45.4%, 5/11 patients with placement across the GEJ). Compared with migration rates reported for covered metallic stents, the migration frequency of SEPS seems to be increased [11,18,20]. However, the migration rates of SEMS are up to 50% when the stent is placed across the GEJ [1,25], which is comparable to our results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In patients with stent placement across the GEJ, the migration rate was even higher (45.4%, 5/11 patients with placement across the GEJ). Compared with migration rates reported for covered metallic stents, the migration frequency of SEPS seems to be increased [11,18,20]. However, the migration rates of SEMS are up to 50% when the stent is placed across the GEJ [1,25], which is comparable to our results.…”
Section: Discussionsupporting
confidence: 80%
“…The most important long-term complication is tumor ingrowth which becomes less frquent since membrane-covered SEMS are used. However, unfortunately the covering of the stents is accompanied by a higher incidence of stent migration [1,18,19].…”
mentioning
confidence: 99%
“…In another prospective trial, the Ultraflex stent and the Flamingo Wallstent were compared in patients with distal esophageal cancer. The two stent types were equally effective in the palliation of dysphagia in this patient group, and the complication rate associated with their use was also comparable (Ultraflex stent: 7/31 (23%) and Flamingo Wallstent: 5/22 (23%)) [29].…”
Section: Consmentioning
confidence: 91%
“…Comparative studies of various types of self-expanding oesophageal stents reported similar rates of efficacy and complications. [175][176][177][178][179][180] Immediate haemorrhage rates are low, but consideration should be given to delayed severe haemorrhage, and this is likely to be a particular risk in patients on APA or anticoagulant therapy.…”
Section: Endoscopic Stent Insertionmentioning
confidence: 99%